Determinants of Online Petition Success in Influencing Public Policy: A Quantitative Analysis - Boby Suherman; Mardian Ismail (IHSA Institute, 2026)
The rapid expansion of digital technologies has transformed political participation by enabling citizens to engage directly in public affairs through online petition platforms. As online petitions become increasingly popular instruments of digital activism and democratic participation, understanding their effectiveness in influencing public policy has become an important area of research. This study examines the effectiveness of online petitions in driving policy change and identifies the factors associated with successful policy outcomes. A quantitative explanatory research design with a cross-sectional approach was employed using secondary data collected from major online petition platforms, government policy databases, and international governance indicators. The study analyzed a purposive sample of 250 online petitions submitted between 2018 and 2025. Data were analyzed using descriptive statistics, correlation analysis, and binary logistic regression to evaluate the influence of petition characteristics on policy change while controlling for relevant political and socioeconomic factors. The findings reveal that online petitions can significantly contribute to policy change; however, their effectiveness depends on multiple interconnected factors. The number of signatures, media coverage, government responsiveness, and political openness were found to have significant positive effects on policy change, whereas petition duration and social media shares did not exhibit statistically significant direct effects. Government responsiveness emerged as the strongest predictor of successful policy outcomes, highlighting the critical role of institutional support in translating digital participation into governmental action. Overall, the study concludes that successful online petitions require not only broad public participation but also supportive political institutions and effective communication strategies.